O przekraczaniu samego siebie i samotności w doświadczeniu rodzicielstwa: On self-transcendence and loneliness in the experience of parenthood - Hucko, Olga (Difficult situation in biographies: Volume 9, 2025)
Based on original research, the author explores selected narratives from the biographies of individuals newly assuming the role of parenthood—mothers and fathers raising their first and only child, no older than three years. The study sheds light on experiences associated with this new life situation, with particular emphasis on the feelings of loneliness and isolation often accompanying parents during this transition. The text conceptualizes parenthood as a challenging situation, a form of limit-experience (cf. Jaspers), and as a monomythic hero’s journey (cf. Campbell). A difficult situation is understood here as one involving a profound challenge—a moment in which the mythic hero responds to the call to adventure, leaves behind the safety of the familiar world, descends into the unknown, and undergoes a transformative trial.